2018
DOI: 10.1111/jace.15717
|View full text |Cite
|
Sign up to set email alerts
|

Strong and super tough: Layered ceramic‐polymer composites with bio‐inspired morphology

Abstract: Bio‐inspired layered ceramic‐polymer composites with high strength and toughness were prepared from sintered aluminum oxide ceramic sheets and cationically curing epoxy resins toughened with poly(ε‐caprolactone) (PCL). The architecture of the composite is inspired by nacre but is arranged on a larger scale. Ceramic sheets with a nominal thickness of 250 μm were assembled into composite plates by adhesive layers with a nominal thickness of 20 μm. Before the manufacturing of the composites, the stress‐strain pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Higher tensile stress in flexible epoxy resin generated a larger stress gradient, which could eliminate stress concentrations in the brittle silicate components. Such reinforcing mechanism primarily accounts for the significant improvement of toughness for biomimetic silicate-epoxy ceramic composites [19,47,48]. As a result, the stress in the section B was divided into two characteristic zones (zone I in tension and zone II in compression) as shown in Fig.…”
Section: Damage Feature Under Fracture Deformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher tensile stress in flexible epoxy resin generated a larger stress gradient, which could eliminate stress concentrations in the brittle silicate components. Such reinforcing mechanism primarily accounts for the significant improvement of toughness for biomimetic silicate-epoxy ceramic composites [19,47,48]. As a result, the stress in the section B was divided into two characteristic zones (zone I in tension and zone II in compression) as shown in Fig.…”
Section: Damage Feature Under Fracture Deformationmentioning
confidence: 99%
“…Inspired by the enamel microstructure, the biomimetic ceramic composites with polymer polyvinyl alcohol serving as an elastic phase has demonstrated high fracture strength (1.6 GPa) and good elongation capacity (6.2%) [15−18]. For instance, the silicatehydrogel biomimetic composites with a unidirectional and highly ordered microstructure realized a significant increase in flexural strength (4.73±0.34 MPa) and toughness (14,071±153 kJ/m 3 ) [19]. The structural biomimetic and flexible modification strategies have offered a combined effective pathway to synergistically enhance strength and toughness of engineering materials beyond the intrinsic brittle limitation of any individual constituent [20−24].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] For instance, Ben et al 13 applied the Florentine mechanical model to advanced ceramic composites, indicating that an appropriate density arrangement of layers would improve the impact resistance. Pogorelov et al 14 reported the bioinspired ceramic-polymer composite achieved excellent toughness performance, which was nearly two times higher than conch-shell, by only adding up to 6.0 vol% of the polymer. However, these bio-inspired composites are common in advanced ceramics, but rarely in traditional ceramic manufacturing due to the high costs of corresponding techniques.…”
Section: Introductionmentioning
confidence: 99%
“…applied the Florentine mechanical model to advanced ceramic composites, indicating that an appropriate density arrangement of layers would improve the impact resistance. Pogorelov et al 14 . reported the bio‐inspired ceramic‐polymer composite achieved excellent toughness performance, which was nearly two times higher than conch‐shell, by only adding up to 6.0 vol% of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial materials that mimic the nacreous architecture of mollusk shells are prominent examples of how evolved hierarchical structures made by living organisms can be harnessed to fabricate synthetic counterparts with outstanding properties and new functionalities 1 3 . By combining design principles of nacre’s brick-and-mortar structure with the rich variety of chemistries available in synthetic systems, current nacre-like materials exhibit mechanical properties that even surpass those of the natural counterparts 4 9 . As opposed to conventional materials, such bio-inspired structures can be designed to showcase antagonistic properties, such as high stiffness and fracture toughness, that are not accessible through the optimization of chemical compositions alone 7 , 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%